2022
DOI: 10.1200/jco.2022.40.16_suppl.9101
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system efficacy of furmonertinib versus gefitinib in patients with non–small cell lung cancer with epidermal growth factor receptor mutations: Results from FURLONG study.

Abstract: 9101 Background: Furmonertinib (AST2818) is a third-generation epidermal growth factor receptor ( EGFR) tyrosine kinase inhibitor (TKI) with central nervous system (CNS) penetration. Here we report the CNS response to furmonertinib versus gefitinib as first-line therapy in EGFR-mutated non-small cell lung cancer (NSCLC) patients in the FURLONG study. Methods: FURLONG was a randomized, double-blind, multi-center phase III study. Patients were randomized 1:1 to receive first-line furmonertinib 80mg/d or gefitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the Chinese Phase III trial FURLONG [ 4 ], compared with gefitinib, the third‐generation EGFR‐TKI furmonertinib in the first‐line treatment of NSCLC with sensitive EGFR mutations can significantly prolong the median progression‐free survival (PFS) (19.3 months vs. 9.9 months, HR = 0.46) and central nervous system PFS (20.8 months vs. 9.8 months, HR = 0.40). Similarly, other third‐generation EGFR‐TKIs, aumolertinib, and nazartinib showed promising results in the AENEAS study [ 5 ] and NCT02108964, respectively, with the median PFS of aumolertinib and nazartinib being 19.3 and 18.0 months, respectively.…”
Section: Epidermal Growth Factor Receptor‐mutated Nsclcmentioning
confidence: 99%
“…In the Chinese Phase III trial FURLONG [ 4 ], compared with gefitinib, the third‐generation EGFR‐TKI furmonertinib in the first‐line treatment of NSCLC with sensitive EGFR mutations can significantly prolong the median progression‐free survival (PFS) (19.3 months vs. 9.9 months, HR = 0.46) and central nervous system PFS (20.8 months vs. 9.8 months, HR = 0.40). Similarly, other third‐generation EGFR‐TKIs, aumolertinib, and nazartinib showed promising results in the AENEAS study [ 5 ] and NCT02108964, respectively, with the median PFS of aumolertinib and nazartinib being 19.3 and 18.0 months, respectively.…”
Section: Epidermal Growth Factor Receptor‐mutated Nsclcmentioning
confidence: 99%
“…Furthermore, aumolertinib demonstrated significantly prolonged median CNS PFS compared with gefitinib (CNS PFS HR, 0.30; 95% CI: 0.137–0.657) ( 90 ). In the phase III FURLONG study, furmonertinib treatment has also demonstrated significantly longer CNS PFS compared with gefitinib (CNS PFS HR, 0.40; 95% CI: 0.23–0.71) ( 91 ). However, overall survival benefit is yet to be demonstrated in these studies.…”
Section: Egfr-tkis To Extend Overall Survival Benefitmentioning
confidence: 99%
“… 21 , 118 Two other third-generation EGFR-TKIs, aumolertinib and furmonertinib, also showed prominent CNS activity in first-line treatment. 119 , 120 In the ANEAS trial, the ORR of aumolertinib in evaluable CNS lesions was 85.7%, and the median CNS-PFS was 29.0 months. In the FURLONG study of furmonertinib, the ORR of measurable CNS lesions was 91%, and the duration of response was 100%.…”
Section: Strategies For Cns Metastasismentioning
confidence: 99%